Effect of protein and ureic nitrogen concentration on milk protein yield - Govea-Luciano, Alejandra; Gómez-Vázquez, Armando; Pinos-Rodrígez, Juan Manuel; Lorenzo-Rodríguez, Jose Manuel; Martínez-Martínez, Ricardo; Rojas-García, Adelaido Rafael (Ecosistemas y Recursos Agropecuarios, 2022)
We aimed to determine the effect of production level (low, medium and high) on milk protein (%), urea nitrogen concentrations (mg dL −1), and milk protein yield of dual- purpose cows (Bos taurus x Bos indicus). We allocated 30 multiparous cows to the following groups by daily milk production level: low (5.0 ± 1.4 kg), medium (7.5 ± 1.0 kg), and high (10.0 ± 1.4 kg). Urea nitrogen did not correlate with milk protein concentrations. Milk protein concentration decreased linearly (p < 0.05) as production level increased. Conversely, milk protein yield (kg day−1) increased linearly (p < 0.05) with production level. Milk urea nitrogen concentrations decreased quadratically (p < 0.05) as production level increased. Low-producing cows had the highest average urea nitrogen concentration. Medium- and high-producing cows had similarly low urea nitrogen concentrations (p > 0.05). Protein and nitrogen concentrations in dual-purpose cow milk are negatively associated with production levels.